A sea-to-soil solution for the green tides threatening shellfish aquaculture: conceptual model and lessons learned from a pilot project - Sarah M. Collier; Emily Buckner; Nicole J. Capizzi; Meg Chadsey; Douglas P. Collins; Jonathan P. Davis; Erick Dowell; Alan Ismach; Brittany G. Johnson; Sergey Rabotyagov; Rob Smith; Katie R. Webb; et al. (Journal of Environmental Management, 2026)

Synthetic biology for sustainable food colourant production: Innovations and opportunities - Bingyin Peng; Ali Jahanian; Thomas R. Collier; Huadong Peng; James B. Behrendorff; Robert E. Speight (Food Chemistry, 2026)

Pharmaceutical Sciences: Insights and Observations from Academic Chairs and Vice Chairs - Kristy M. Ainslie; Albert A Bowers; Robert H. Chichewicz; Lara S. Collier; Jonathan A. Doorn; Christopher R. Frei; Hamidreza Ghandehari; Robert B. Gibbs; David S. Lawrence; Craig R. Lee; Donald E. Mager; Paul Marker; et al. (The AAPS Journal, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A new deglacial climate and sea-level record from 20 to 8 ka from IODP381 site M0080, Alkyonides Gulf, eastern Mediterranean - Ilaria Mazzini; Thomas M. Cronin; Robert L. Gawthorpe; Richard E. Ll Collier; Gino de Gelder; Anna Rose Golub; Michael R. Toomey; Robert K. Poirier; Huai-Hsuan May Huang; Marcie Purkey Phillips; Lisa C. McNeill; Donna J. Shillington (Quaternary Science Reviews, 2023)

Observational constraints reduce model spread but not uncertainty in global wetland methane emission estimates - Kuang‐Yu Chang; William J. Riley; Nathan Collier; Gavin McNicol; Etienne Fluet‐Chouinard; Sara H. Knox; Kyle B. Delwiche; Robert B. Jackson; Benjamin Poulter; Marielle Saunois; Naveen Chandra; Nicola Gedney; et al. (Global Change Biology, 2023)
The recent rise in atmospheric methane (CH 4 ) concentrations accelerates climate change and offsets mitigation efforts. Although wetlands are the largest natural CH 4 source, estimates of global wetland CH 4 emissions vary widely among approaches taken by bottom‐up (BU) process‐based biogeochemical models and top‐down (TD) atmospheric inversion methods. Here, we integrate in situ measurements, multi‐model ensembles, and a machine learning upscaling product into the International Land Model Benchmarking system to examine the relationship between wetland CH 4 emission estimates and model performance. We find that using better‐performing models identified by observational constraints reduces the spread of wetland CH 4 emission estimates by 62% and 39% for BU‐ and TD‐based approaches, respectively. However, global BU and TD CH 4 emission estimate discrepancies increased by about 15% (from 31 to 36 TgCH 4 year −1 ) when the top 20% models were used, although we consider this result moderately uncertain given the unevenly distributed global observations. Our analyses demonstrate that model performance ranking is subject to benchmark selection due to large inter‐site variability, highlighting the importance of expanding coverage of benchmark sites to diverse environmental conditions. We encourage future development of wetland CH 4 models to move beyond static benchmarking and focus on evaluating site‐specific and ecosystem‐specific variabilities inferred from observations.

Application of a 3D hydrogel-based model to replace use of animals for passaging patient-derived xenografts - Sal Jones; Jennifer C. Ashworth; Marian Meakin; Pamela Collier; Catherine Probert; Alison A. Ritchie; Catherine L. R. Merry; Anna M. Grabowska (In vitro models, 2023)
Purpose This 3D in vitro cancer model for propagation of patient-derived cells, using a synthetic self-assembling peptide gel, allows the formation of a fully characterised, tailorable tumour microenvironment. Unlike many existing 3D cancer models, the peptide gel is inert, apart from molecules and motifs deliberately added or produced by cells within the model. Methods Breast cancer patient-derived xenografts (PDXs) were disaggregated and embedded in a peptide hydrogel. Growth was monitored by microscopic examination and at intervals, cells were extracted from the gels and passaged on into fresh gels. Passaged cells were assessed by qPCR and immunostaining techniques for the retention of characteristic markers. Results Breast cancer PDXs were shown to be capable of expansion over four or more passages in the peptide gel. Contaminating mouse cells were found to be rapidly removed by successive passages. The resulting human cells were shown to be compatible with a range of common assays useful for assessing survival, growth and maintenance of heterogeneity. Conclusions Based on these findings, the hydrogel has the potential to provide an effective and practical breast cancer model for the passage of PDXs which will have the added benefits of being relatively cheap, fully-defined and free from the use of animals or animal products. Encapsulated cells will require further validation to confirm the maintenance of cell heterogeneity, genotypes and phenotypes across passage, but with further development, including the addition of bespoke cell and matrix components of the tumour microenvironment, there is clear potential to model other cancer types.

Central arterial stiffness, wave reflection, and heart rate variability following 4-week high-intensity resistance training intervention in young active women - Sarean Harmoni A. Gaynor-Metzinger; N. Travis Triplett; Marco Meucci; Kimberly S. Fasczewski; Damon H. Flinchum; Scott R. Collier (European Journal of Applied Physiology, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The palaeoshoreline of Early Miocene formations (Euphrates and Jeribe) at the periphery of the Zagros Foreland Basin, Sulaimani Governorate, Kurdistan Region, NE Iraq - H. G. Abdullah; R. E. L. Collier; N. P. Mountney (Arabian Journal of Geosciences, 2019)
A sedimentological investigation of the Early Miocene deposits at the periphery of the Zagros Foreland Basin, Kurdistan Region, around Qishlagh-Sargrma and Darbandikhan, reveals the presence of the Euphrates and Jeribe Formations in this area. A carbonate-dominated unit, comprising four regressive carbonate cycles, at the base of the Fatha Formation, has been investigated to characterize the depositional environments and stratigraphic context of these Early Miocene deposits. Outcrop and thin-section analyses of the carbonate succession reveal a gently inclined, carbonate-dominated ramp based on the depositional lithofacies and microfacies. Eight carbonate microfacies were identified and interpreted to have been deposited in a shallow marine environment. The Euphrates Formation passes up from deposits of restricted lagoon to shoal depositional environments, while the Jeribe Formation was deposited in a hypersaline lagoon to a restricted lagoon. The Early Miocene index fossil Borelis melo melo was identified in the deposits of the Euphrates Formation. Stratigraphic correlation of the studied sections allows the development of a revised palaeogeography for the Early Miocene deposits in the Kurdistan Region.

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Neuroprotective activity of leukemia inhibitory factor is relayed through myeloid zinc finger-1 in a rat model of stroke - Stephanie M. Davis; Lisa A. Collier; Elspeth A. Foran; Christopher C. Leonardo; Craig T. Ajmo; Keith R. Pennypacker (Metabolic Brain Disease, 2019)

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Stratigraphic correlation and paleoenvironmental analysis of the hydrocarbon-bearing Early Miocene Euphrates and Jeribe formations in the Zagros folded-thrust belt - D. Hussein; R. Collier; J. A. Lawrence; F. Rashid; P. W. J. Glover; P. Lorinczi; D. H. Baban (Arabian Journal of Geosciences, 2017)

Early life traits of farm and wild A tlantic salmon S almo salar and first generation hybrids in the south coast of N ewfoundland - D. Hamoutene; J. Perez‐Casanova; K. Burt; L. Lush; J. Caines; C. Collier; R. Hinks (Journal of Fish Biology, 2017)
This study examined fertilization rates, survival and early life‐trait differences of pure farm, wild and first generation ( F1 ) hybrid origin embryos after crossing farm and wild Atlantic salmon Salmo salar . Results show that despite a trend towards higher in vitro fertilization success for wild females, differences in fertilization success in river water are not significantly different among crosses. In a hatchery environment, wild females' progeny (pure wild and hybrids with wild maternal parent) hatched 7–11 days earlier than pure farm crosses and hybrids with farm maternal parents. In addition, pure wild progeny had higher total lengths ( L T ) at hatch than pure farm crosses and hybrids. Directions in trait differences need to be tested in a river environment, but results clearly show the maternal influence on early stages beyond egg‐size differences. Differences in L T were no longer significant at 70 days post hatch (shortly after the onset of exogenous feeding) showing the need to investigate later developmental stages to better assess somatic growth disparities due to genetic differences. Higher mortality rates of the most likely hybrids (farm female × wild male hybrids) at egg and fry stages and their delayed hatch suggest that these F1 hybrids might be less likely to survive the early larval stages than wild stocks.

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Leukemia Inhibitory Factor Protects Neurons from Ischemic Damage via Upregulation of Superoxide Dismutase 3 - Stephanie M. Davis; Lisa A. Collier; Christopher C. Leonardo; Hilary A. Seifert; Craig T. Ajmo; Keith R. Pennypacker (Molecular Neurobiology, 2017)

Belowground interactions between Kalmia angustifolia and Picea mariana: roles of competition, root exudates and ectomycorrhizal association - Azim U. Mallik; Shekhar R. Biswas; Laura C. Siegwart Collier (Plant and Soil, 2016)

Following Natures Lead: On the Construction of Membrane-Inserted Toxins in Lipid Bilayer Nanodiscs - Narahari Akkaladevi; Srayanta Mukherjee; Hiroo Katayama; Blythe Janowiak; Deepa Patel; Edward P. Gogol; Bradley L. Pentelute; R. John Collier; Mark T. Fisher (The Journal of Membrane Biology, 2015)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

Phenological decoupling of mortality from wave forcing in kelp beds - Thibaut de Bettignies; Thomas Wernberg; Paul S. Lavery; Mathew A. Vanderklift; Jim R. Gunson; Graham Symonds; Neil Collier (Ecology, 2015)
Kelps often live in a harsh hydrodynamic environment where wave‐driven dislodgement of individuals can alter the biodiversity and functioning of reef systems, and increase production in coastal ecosystems adjacent to reefs. The current paradigm is that winter storms tear kelps from reefs once hydrodynamic forces exceed attachment or tissue strength—a threshold response that implies a pulsed relationship between wave forces and dislodgement. Here, we challenge this understanding by showing how kelp phenology can decouple susceptibility to dislodgement from seasonal patterns in wave forces. We measured kelp dislodgement rates and hydrodynamic forces at nine subtidal reefs over two years ( n = 4320 kelps tagged and monitored). Contrary to expectation, we found relatively low and constant dislodgement rates for all reefs (13% ± 6% [mean per season ± SD]) in spite of a strong temporal pattern in wave action and extreme water velocities (winter peaks up to 3–4 m/s). A biomechanical model, based on the balance between kelp attachment strength and hydrodynamic drag, demonstrated that severe reduction in individual kelp size toward winter (>50% decrease in biomass for all sites) minimized drag and made the kelps less susceptible to high water velocities, allowing individuals to survive storm velocities over 3–4 m/s. We conclude that the timing of reduced susceptibility to disturbance, through the seasonal reduction of individual kelp biomass that coincides with times of highest water velocities is critical to the dynamics of kelp dislodgement and survival. We propose that phenological processes maintain many kelp beds in a higher degree of population stability and equilibrium with hydrodynamic forces than previously believed.

Pro-Inflammatory Interferon Gamma Signaling is Directly Associated with Stroke Induced Neurodegeneration - Hilary A. Seifert; Lisa A. Collier; Cortney B. Chapman; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Journal of Neuroimmune Pharmacology, 2014)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Natural variations in xenobiotic-metabolizing enzymes: developing tools for coral monitoring - L. R. A. Rougée; R. H. Richmond; A. C. Collier (Coral Reefs, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

A Transient Decrease in Spleen Size Following Stroke Corresponds to Splenocyte Release into Systemic Circulation - Hilary A. Seifert; Aaron A. Hall; Cortney B. Chapman; Lisa A. Collier; Alison E. Willing; Keith R. Pennypacker (Journal of Neuroimmune Pharmacology, 2012)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

CCL20 Is Associated with Neurodegeneration Following Experimental Traumatic Brain Injury and Promotes Cellular Toxicity In Vitro - Christopher C. Leonardo; James Musso; Mahasweta Das; Derrick D. Rowe; Lisa A. Collier; Shyam Mohapatra; Keith R. Pennypacker (Translational Stroke Research, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Characterisation of amyloid-induced inflammatory responses in the rat retina - D. R. Howlett; S. T. Bate; S. Collier; A. Lawman; T. Chapman; T. Ashmeade; I. Marshall; P. J. B. Anderson; K. L. Philpott; J. C. Richardson; C. J. Hille (Experimental Brain Research, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Contemporary habitat loss reduces genetic diversity in an ecologically specialized butterfly - Neil Collier; Mike Gardner; Mark Adams; Clive R. McMahon; Kirsten Benkendorff; Duncan A. Mackay (Journal of Biogeography, 2010)
Aim This study investigated the influence of contemporary habitat loss on the genetic diversity and structure of animal species using a common, but ecologically specialized, butterfly, Theclinesthes albocincta (Lepidoptera: Lycaenidae), as a model. Location South Australia. Methods We used amplified fragment length polymorphism (AFLP) and allozyme datasets to investigate the genetic structure and genetic diversity among populations of T. albocincta in a fragmented landscape and compared this diversity and structure with that of populations in two nearby landscapes that have more continuous distributions of butterflies and their habitat. Butterflies were sampled from 15 sites and genotyped, first using 363 informative AFLP bands and then using 17 polymorphic allozyme loci ( n = 248 and 254, respectively). We complemented these analyses with phylogeographic information based on mitochondrial DNA (mtDNA) haplotype information derived from a previous study in the same landscapes. Results Both datasets indicated a relatively high level of genetic structuring across the sampling range (AFLP, F ST = 0.34; allozyme, F ST = 0.13): structure was greatest among populations in the fragmented landscape (AFLP, F ST = 0.15; allozyme, F ST = 0.13). Populations in the fragmented landscape also had significantly lower genetic diversity than populations in the other two landscapes: there were no detectable differences in genetic diversity between the two continuous landscapes. There was also evidence ( r 2 = 0.33) of an isolation by distance effect across the sampled range of the species. Main conclusions The multiple lines of evidence, presented within a phylogeographic context, support the hypothesis that contemporary habitat fragmentation has been a major driver of genetic erosion and differentiation in this species. Theclinesthes albocincta populations in the fragmented landscape are thus likely to be at greater risk of extinction because of reduced genetic diversity, their isolation from conspecific subpopulations in other landscapes, and other extrinsic forces acting on their small population sizes. Our study provides compelling evidence that habitat loss and fragmentation have significant rapid impacts on the genetic diversity and structure of butterfly populations, especially specialist species with particular habitat preferences and poor dispersal abilities.

Improved simulation of Australian climate and ENSO‐related rainfall variability in a global climate model with an interactive aerosol treatment - Leon D. Rotstayn; Mark A. Collier; Martin R. Dix; Yan Feng; Hal B. Gordon; Siobhan P. O'Farrell; Ian N. Smith; Jozef Syktus (International Journal of Climatology, 2010)
We assess the simulation of Australian mean climate and rainfall variability in a new version of the CSIRO coupled ocean–atmosphere global climate model (GCM). The new version, called Mark 3.6 (Mk3.6), differs from its recent predecessors (Mk3.0 and Mk3.5) by inclusion of an interactive aerosol scheme, which treats sulfate, dust, sea salt and carbonaceous aerosol. Other changes include an updated radiation scheme and a modified boundary‐layer treatment. Comparison of the mean summer and winter climate simulations in Mk3.6 with those in Mk3.0 and Mk3.5 shows several improvements in the new version, especially regarding winter rainfall and sea‐level pressure. The improved simulation of Australian mean seasonal climate is confirmed by calculation of a non‐dimensional skill score (the ‘ M ‐statistic’), using data from all four seasons. However, the most dramatic improvement occurs in the model's simulation of the leading modes of annual rainfall variability, which we assess using empirical orthogonal teleconnections (EOTs). Compared to its predecessors and several international GCMs, Mk3.6 is best able to capture the spatial pattern of the leading rainfall mode, which represents variability due to the El Niño Southern Oscillation (ENSO). Mk3.6 is also best able to capture the spatial pattern of the second rainfall mode, which corresponds to increased rainfall in the northwest, and decreased rainfall over eastern Australia. We propose a possible mechanism for the improved simulation of rainfall variability in terms of the role of interactive dust in Mk3.6. By further suppressing convection over eastern Australia during El Niño events, dust feedbacks may enhance rainfall variability there, in tune with the model's ENSO cycle. This suggests that an interactive aerosol treatment may be important in a GCM used for the study of Australian climate change and variability. Mechanistic sensitivity studies are needed to further evaluate this hypothesis. Copyright © 2009 Royal Meteorological Society

Administration of a Sigma Receptor Agonist Delays MCAO-Induced Neurodegeneration and White Matter Injury - Christopher C. Leonardo; Aaron A. Hall; Lisa A. Collier; Suzanne M. Green; Alison E. Willing; Keith R. Pennypacker (Translational Stroke Research, 2010)

Genetic variation in PARL influences mitochondrial content - Joanne E. Curran; Jeremy B. M. Jowett; Lawrence J. Abraham; Luke A. Diepeveen; Katherine S. Elliott; Thomas D. Dyer; Lyndal J. Kerr-Bayles; Matthew P. Johnson; Anthony G. Comuzzie; Eric K. Moses; Ken R. Walder; Gregory R. Collier; et al. (Human Genetics, 2010)

Characterization of Phytophthora infestans Isolates from Jersey, Channel Islands - Kenneth L. Deahl; Frances M. Perez; Jonathan M. Thompson; Caoimhe Fleming-Archibald; Stephen Thompson; Rosemary Collier; Steven Kildea; Louise R. Cooke (Potato Research, 2009)

Localization and expression of selenoprotein S in the testis of Psammomys obesus - Kelly Windmill; Janette Tenne-Brown; Richard Bayles; James Trevaskis; Yuan Gao; Ken Walder; Greg R. Collier (Journal of Molecular Histology, 2007)

Contaminant exposure in outmigrant juvenile salmon from Pacific Northwest estuaries of the United States - Lyndal L. Johnson; Gina M. Ylitalo; Mary R. Arkoosh; Anna N. Kagley; Coral Stafford; Jennie L. Bolton; Jon Buzitis; Bernadita F. Anulacion; Tracy K. Collier (Environmental Monitoring and Assessment, 2007)

Predicting Secchi disk depth from average beam attenuation in a deep, ultra-clear lake - Gary L. Larson; Robert L. Hoffman; Bruce R. Hargreaves; Robert W. Collier (Hydrobiologia, 2007)

Ultraviolet radiation and bio-optics in Crater Lake, Oregon - B. R. Hargreaves; S. F. Girdner; M. W. Buktenica; R. W. Collier; E. Urbach; G. L. Larson (Hydrobiologia, 2007)

The extent and significance of petroleum hydrocarbon contamination in Crater Lake, Oregon - Daniel R. Oros; Robert W. Collier; Bernd R. T. Simoneit (Hydrobiologia, 2007)

Long-term observations of deepwater renewal in Crater Lake, Oregon - G. B. Crawford; R. W. Collier (Hydrobiologia, 2007)

Pleistocene subglacial tunnel valleys in the central North Sea basin: 3‐D morphology and evolution - Lidia Lonergan; Susannah C. R. Maidment; Jenny S. Collier (Journal of Quaternary Science, 2006)
Four phases of cross‐cutting tunnel valleys imaged on 3‐D seismic datasets are mapped within the Middle–Late Pleistocene succession of the central North Sea basin (Witch Ground area). In plan the tunnel valleys form complex anastomosing networks, with tributary valleys joining main valleys at high angles. The valleys have widths ranging from 250 to 2300 m, and base to shoulder relief varying between 30 and 155 m, with irregular long‐axis profiles characteristic of erosion by water driven by glaciostatic pressures. The youngest phase of tunnel valleys are smaller and have a thinner infill than the older generations. The fill of the larger valleys comprises three seismic facies, the lowermost of which has high amplitudes and is discontinuous. The middle facies consists of wedge‐shaped packages of low‐angle dipping reflectors and is overlain by a facies characterised by sub‐horizontal reflectors, which onlap the valley margins. The seismic character, and comparison with lithologies identified in other northwest European Pleistocene tunnel valleys both onshore and offshore, suggests that the lower two seismic facies are most likely sand and gravel‐dominated, while the uppermost facies consists of glaciolacustrine and marine muds. The 3‐D morphology of the valley margins combined with the geometry of the infill packages suggest that episodic discharge of subglacial meltwater was responsible for incising the valleys and depositing at least some of the infill. Proglacial glaciofluvial deposits are inferred to account for some of the fill overlying the subglacial deposits. Glaciolacustrine and marine muds filled remaining valley topography as the ice sheet retreated. The preserved valley margins are shown to be time‐transgressive erosion surfaces that record changes in geometry of the tunnel valley system as it evolved through time, implying that valleys associated with each ice‐sheet advance/retreat cycle were dynamic and probably long‐lived. Within the constraints of the existing stratigraphy the oldest tunnel valleys in the Witch Ground area of the central North Sea are most likely to be Marine Isotope Stage (MIS) 12 (Elsterian, ca. 470 ka) in age and the youngest pre‐MIS 5e (last interglacial, ca. 120 ka). If each tunnel valley phase was formed during the retreat of a major ice sheet then four glaciations with ice coverage of the central North Sea are recorded in the pre‐Weichselian, Middle–Late Pleistocene stratigraphy. Copyright © 2006 John Wiley & Sons, Ltd.

Sex differences in muscle fatigability and activation patterns of the human quadriceps femoris - Brian C. Clark; Scott R. Collier; Todd M. Manini; Lori L. Ploutz-Snyder (European Journal of Applied Physiology, 2005)

Effects of forest harvesting and woody debris removal on two Northland streams, New Zealand - Brenda R. Baillie; Kevin J. Collier; John Nagels (New Zealand Journal of Marine and Freshwater Research, 2005)
The short‐term effects of Pinus radiata forest harvesting to the stream edge followed by stream‐cleaning (removal of woody debris from the stream channel), on instream light levels, stream temperature, dissolved oxygen concentrations, and aquatic invertebrates were assessed in streams draining partly (25% clear‐cut) and totally (100% clear‐cut) harvested catchments, compared with nearby indigenous forest and mature pine plantation reference sites. There were marked increases in in‐stream light levels and water temperatures following forest harvest and stream‐cleaning at both sites. In‐stream light levels increased from 8–13% to 60–90% and maximum monthly water temperatures increased on average by 5.6°C in the partly harvested and 3.6°C in the fully harvested catchment. Dissolved oxygen levels decreased at both sites shortly after harvest (94%‐71% saturation in the partly harvested catchment; 72%‐37% saturation in the totally harvested catchment), increasing to 75% and 81%, respectively, 1 year later. Although aquatic invertebrate mean density and taxa richness increased at both sites following harvest, the relative abundance of sensitive mayfly, caddisfly, and stonefly species decreased and community composition changed to one dominated by Chironomidae (midges) or Mollusca. Impacts relative to pre‐harvest conditions were not as marked in the totally harvested catchment, possibly because of pre‐existing elevated stream temperatures and high levels of sand and silt. Any downstream protection provided by the forested headwaters of the partly harvested catchment was soon lost after the stream entered the clear‐cut area, although these forested headwaters may provide a potential source of aquatic invertebrates for re‐colonisation in the future as water quality and habitat recover. Our results suggest that: (1) pre‐existing constraints on habitat quality can influence the magnitude of harvesting impacts; and (2) length of stream edge harvested may be a better indicator of impact on some aspects of stream ecology, such as lighting, stream temperature, dissolved oxygen, and aquatic invertebrate community composition, than percentage of catchment harvested. This study also highlights the importance of considering the hydro‐logical and landscape context for mitigating harvesting and wood management impacts on stream ecosystems.

Clinical validation of the NeuroScreen - Ronald J Ellis; Scott R Evans; David B Clifford; Lauren R Moo; Justin C McArthur; Ann C Collier; Constance Benson; Ron Bosch; David Simpson; Constantin T Yiannoutsos; Yijun Yang; Kevin Robertson; et al. (Journal of NeuroVirology, 2005)

Ecoregional differences in macrophyte and macroinvertebrate communities between Westland and Waikato: Are all New Zealand lowland streams the same? - I. C. Duggan; K. J. Collier; P. D. Champion; G. F. Croker; R. J. Davies‐Colley; P. W. Lambert; J. W. Nagels; R. J. Wilcock (New Zealand Journal of Marine and Freshwater Research, 2002)
We characterised water chemistry, aquatic habitat, macrophytes, and invertebrate assemblages in eight lowland streams—five in Westland, South Island, and three in the Waikato, North Island, New Zealand. Factors influencing invertebrate community structure over large (between ecoregions) and small (within an ecoregion) spatial scales were investigated. The Westland sites had generally lower nutrient concentrations, conductivity, and water clarity, and coarser substrates than the Waikato sites, reflecting differences in geological history, hydrology, and land‐use intensity. The macrophyte communities in each region were very different in species composition and structure, but seasonal abundance patterns in both regions were fairly typical of New Zealand streams in general. Alien obligate submerged macrophyte species were absent from the Westland lowland stream sites, and may partly reflect the isolated nature of this region where colonisation by asexual macrophytes would be difficult. Waikato stream invertebrate faunas were dominated by molluscs (mainly Potamopyrgus ) and crustaceans (mainly amphipods), whereas Epheme‐roptera, Trichoptera, and Coleoptera taxa dominated the Westland stream faunas. The overall structure of invertebrate assemblages appeared to be influenced by a combination of regional differences in substrate type, nutrient concentrations, water clarity, and macrophyte cover. Westland streams with more upstream pastoral development had higher proportions of molluscs than those with predominantly forested or scrub catchments. Our study suggests that large‐scale ecoregional differences may override smaller‐scale land‐use effects on lowland stream invertebrate communities, and that management strategies should be developed on an ecoregional basis for lowland stream ecosystems.

Diet of the crayfish Paranephrops zealandicus in bush and pasture streams: Insights from stable isotopes and stomach analysis - John W. Hollows; Colin R. Townsend; Kevin J. Collier (New Zealand Journal of Marine and Freshwater Research, 2002)
Crayfish ( Paranephrops zealandicus White) stomachs from streams in both native bush (mainly tree leaves and dicotyledonous seeds) and exotic pasture settings (mainly grass stems and monocotyledonous seeds) were dominated by allochthonous material. More detritus occurred in stomachs in autumn‐winter than in spring‐summer, but quantities were similar in crayfish from native bush and pasture streams. The stomachs of larger crayfish contained a significantly greater proportion of detritus than smaller individuals. Aquatic invertebrates were the second most abundant dietary category by volume, with highest values in winter, but there were no significant differences between land uses or crayfish size classes. A wide range of invertebrates was eaten by crayfish, with mayfly nymphs, chironomid larvae, and snails predominating. The latter were numerically more prominent in crayfish from bush than pasture streams. Terrestrial invertebrates were recorded from 4% of stomachs, but there were no significant differences in relation to land use, season, or crayfish size class. Despite aquatic invertebrates making up 13 C and perhaps of microfloral origin, seems to be an important energy source for crayfish in both stream types.

Lethal interference competition in the whitefly parasitoids Eretmocerus eremicus and Encarsia sophia - Timothy R. Collier; Martha S. Hunter (Oecologia, 2001)

UV radiation and potential biological effects beneath the perennial ice cover of an antarctic lake - R. L. Kepner; R. A. Wharton; R. D. Collier; C. S. Cockell; W. H. Jeffrey (Hydrobiologia, 2000)

Summer light‐trap catches of adult Trichoptera in hill‐country catchments of contrasting land use, Waikato, New Zealand - Kevin J. Collier; Brian J. Smith; Brenda R. Baillie (New Zealand Journal of Marine and Freshwater Research, 1997)
The distribution of adult Trichoptera in light traps was investigated alongside nine streams draining catchments under native forest, pine forest, or pasture near Hamilton, Waikato, New Zealand. The aim of the study was to determine the relationship between abundance, taxonomic richness, and community composition with respect to land use during summer, and to evaluate the use of adult Trichoptera compared with benthic invertebrates as potential bio‐indicators of the effectiveness of land‐management changes. Adult Trichoptera faunas alongside the native streams were dominated by Hydrobiosidae, Conoesucidae, and Helicopsychidae (each >10% of total Trichoptera numbers for at least two of the three sites), whereas Leptoceridae, Oeconescidae, and Hydrobiosidae were relatively abundant alongside at least two of the pine sites. Adult Trichoptera faunas at the pasture sites were strongly dominated by Hydroptilidae which made up 47–85% of numbers caught at all sites. The mean number of individuals and taxa caught in light traps increased from November to January and then declined in February for all land‐use types. Overall, total numbers and taxonomic richness of adult Trichoptera were significantly lower at the pine sites compared to the pasture or native sites. TWINSPAN classification of benthic invertebrates collected in November clearly differentiated sites based on land use for presence/absence and percentage abundance data. A similar pattern was evident for most sites when adult Trichoptera faunas were used for the four sampling dates combined, suggesting that light trapping has potential as a tool for bio‐monitoring.

Observations of a deep‐mixing event in Crater Lake, Oregon - G. B. Crawford; R. W. Collier (Limnology and Oceanography, 1997)
We present observations of the evolution of a deep‐mixing event in a deep, temperate lake. The observations were obtained from thermistors mounted on a long‐term mooring in the lake. The event seems to have originated near 150‐m depth and resulted in a plume or layer of cold water from the upper half of the lake that descended to the lake bottom (590 m) over a 3‐d period. Net mixing associated with this event resulted in an overall vertical heat exchange of nearly 10 15 J and a volume exchange of 0.7–3.2 km 3 (4–18% of the lake volume) between the upper and lower portions of the lake. The deep water displaced during the event is estimated to have carried 0.3–2.5 × 10 6 mol of nitrate to the upper lake, which accounts for a significant portion of the average annual nitrate flux (∼2–4 × 10 6 mol yr −1 ) thought to be upwelled in this highly oligotrophic system.

Cytoplasmic and mitochondrial arginine kinases inDrosophila: Evidence for a single gene - Lori R. Munneke; Glen E. Collier (Biochemical Genetics, 1988)

Genetic and biochemical characterization of phosphofructokinase from Drosophila melanogaster - Lori R. Munneke; Glen E. Collier (Biochemical Genetics, 1985)